If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = -12x Reorder the terms: -7 + x = -12x Solving -7 + x = -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -7 + x + 12x = -12x + 12x Combine like terms: x + 12x = 13x -7 + 13x = -12x + 12x Combine like terms: -12x + 12x = 0 -7 + 13x = 0 Add '7' to each side of the equation. -7 + 7 + 13x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 13x = 0 + 7 13x = 0 + 7 Combine like terms: 0 + 7 = 7 13x = 7 Divide each side by '13'. x = 0.5384615385 Simplifying x = 0.5384615385
| -5x^2-5x-10=0 | | c=15n+5 | | .7-4y=1.74 | | 3c=19+-2 | | 6x^3+37x^2-34x+7=0 | | 900=45m | | 8-2y=40 | | 27=-y/7 | | 2f-7=13 | | 1.6a+(-4)=.32 | | 0=(2x-3)(x+5) | | Z+11=25 | | Z+11=209 | | 11y=209 | | 2/5×3/9 | | 9x^2-72x-16y^2-32=16 | | P/90=8/18 | | Y+8(y-9)= | | y=3x(x-5) | | Z+10=12 | | -14g=406 | | -12x-8=15x-2 | | 2/100=b/200 | | 2+12=25 | | -60=-15h | | -4=3m+2 | | Y-17=3 | | -68=17c | | 2x^2+28x+20=0 | | 4x^2-2x+4y^2+16y+13=0 | | 25=-2+12 | | 8(5-1)= |